Modulation of the ligand-independent activation of the human estrogen receptor by hormone and antihormone. - Smith, C L (1993)
It has been previously demonstrated that several members of the steroid receptor superfamily may be activated by the neurotransmitter dopamine in the apparent absence of cognate ligand. We have examined wild-type and mutant human estrogen receptors (ERs, [Gly400]ER and [Val400]ER, respectively) for their abilities to activate ER-dependent transcription of a transgene in a ligand-independent manner. In cells expressing the wild-type ER, dopamine was nearly as effective as 17 beta-estradiol at inducing the chloramphenicol acetyltransferase activity of the reporter gene in a dose-dependent manner; simultaneous addition of suboptimal concentrations of 17 beta-estradiol and dopamine stimulated transcription more than either compound alone. Dopamine alone was unable to induce gene expression in cells expressing [Val400]ER mutant receptors, but concomitant treatment with 17 beta-estradiol produced a synergistic increase in transcription, suggesting that the ligand may alter the mutant receptor's conformation such that it can be activated subsequently by a dopaminergic signaling mechanism. In the presence of the antiestrogen ICI 164,384, dopamine-stimulated gene expression was undetectable in cells expressing either form of ER. However, simultaneous treatment of cells expressing wild-type ER with trans-4-hydroxytamoxifen and dopamine resulted in transgene expression that was additive in nature compared to either compound alone; similar treatment of cells expressing [Val400]ER produced a synergistic increase. Our results suggest that ligand and ligand-independent activation of the ER initiate from distinct pathways and that the latter may occur in a variety of target tissues subject to modulation by receptor ligands.